2014
DOI: 10.2169/internalmedicine.53.2591
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Disturbances and Abdominal Symptoms

Abstract: Objective Although gastroesophageal reflux disease (GERD) is known to cause sleep disturbances, the relationships between other abdominal symptoms and sleep disorders have not been clarified. In the present study, we examined the relationships between daytime sleepiness and various abdominal symptoms in a nonclinical population. Methods We enrolled 2,936 subjects who visited Matsue Red Cross Hospital for an annual health check examination during a 10-month consecutive period after excluding those with organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
(42 reference statements)
0
26
0
Order By: Relevance
“…Numerous studies have demonstrated a strong association between SD and functional gastrointestinal disorders including GERD, FD, and IBS [1][2][3]. These disorders can affect the sleep-wake cycle and lead to poor quality of sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated a strong association between SD and functional gastrointestinal disorders including GERD, FD, and IBS [1][2][3]. These disorders can affect the sleep-wake cycle and lead to poor quality of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in sleep phenomenology and its relation to gastrointestinal functioning has recently increased. A number of studies have demonstrated a strong association between SD and functional gastrointestinal disorders [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, ulcer-like dyspepsia, diarrhea-predominant IBS, alternating IBS, functional constipation, and GERD were found to be significantly associated with EDS, which was in consistency with a similar previous study. 17 Furthermore, we applied the Rome II criteria and RDQ to diagnose FGIDs so that we were able to divide FD and IBS into more specific subtypes in order to avoid confusion of similar diseases, such as diarrhea-predominant IBS and functional diarrhea, constipation-predominant IBS, and functional constipation. 29,30 Overweight and obesity were significantly associated with EDS.…”
Section: Discussionmentioning
confidence: 99%
“…16 Presence of FD and IBS symptoms in addition to GERD symptoms exhibited a strong relationship with daytime sleepiness in Japanese. 17 In Israel, IBS patients tended to suffer from daytime sleepiness measured by the Epworth Sleepiness Scale (ESS). 18 EDS is a common sleep-related symptom in China, it is more prevalent in the general Chinese population (22.2%) than in general American (8.7%) and Japanese populations (2.5%).…”
Section: Introductionmentioning
confidence: 99%